Extended age model, avalanche chronicle and pebble count of Lake Lauvitel sediments - Laurent Fouinat; Pierre Sabatier; Fernand David; Xavier Montet; Philippe Schoeneich; Eric Chaumillon; Jérôme Poulenard; Fabien Arnaud (PANGAEA, 2018)
Understanding wet avalanche intensity and the role of past environmental changes on wet avalanche occurrence is a main concern especially in the context of a warming climate and accelerated environmental mutations. Avalanches are closely related to fast cryosphere changes and may cause major threats to human society. Here, we used the sedimentary archive of the alpine Lake Lauvitel (western French Alps) to establish the first long-term avalanche record in this Alpine region. For this purpose, we used a novel CT scan methodology that allows the precise identification of coarse material - from sand to pebble - transported to the lake and embedded within the finer continuous sedimentation. We identified a total of 166 deposits over the last 3300 yrs cal. BP. In parallel, a detailed pollen analysis gave an independent record of environmental changes. Based on modern observation, lake monitoring, seismic investigations and sedimentological evidences, coarse material deposits were attributed to wet avalanche events. Our results highlight the effect of vegetation cover on the avalanche hazard while a period of strong frequency increase occurred after 780 yrs cal. BP. In Lake Lauvitel, this period corresponds to a major forest clearance induced by the rise of human land-use. Climate forcing on the avalanche hazard was investigated before and after the vegetation shift. On a multi-centennial scale, wet avalanches preferably occur during periods of larger glacier extent, in which higher winter precipitations probably generate a sufficiently thick snow cover. On a sub-centennial scale, avalanches are more frequent during periods of relative warming, resulting in a destabilisation of the same snow cover in spring season. Our results highlight as well the role of forest cover to mitigate wet snow avalanches occurrence. In the context of predicted warmer temperatures, this study raises the question of whether a wet avalanche hazard increase may be expected in the near future especially at higher altitudes.
Supplement to: Fouinat, L et al. (2018): Wet avalanches: long-term evolution in the Western Alps under climate and human forcing. Climate of the Past, 14(9), 1299-1313, https://doi.org/10.5194/cp-14-1299-2018